2011
DOI: 10.3892/ijmm.2010.571
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin exerts a neuroprotective effect through inhibition of the iNOS/NO system and pro-inflammation gene expression in PC12 cells and in zebrafish

Abstract: Abstract.Flavonoids have been reported to be potent antioxidants and beneficial in the treatment of oxidative stress-related diseases. Quercetin, a major flavonoid naturally occurring in plants, deserves attention because of its beneficial effects observed in various in vitro and in vivo neural damage models; however, the actions of quercetin are paradoxical. In an effort to confirm the neuroprotective effect of quercetin and to elucidate its mechanism of action, the neuroprotective effects of quercetin in PC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 46 publications
(50 reference statements)
1
41
0
Order By: Relevance
“…QUE can attenuate liver injury [56] and renal impairment [57], [58], and provide neuroprotective protection against excitotoxic insults [59], [60]. KAE can also provide cardio- and neuro-protections [61].…”
Section: Discussionmentioning
confidence: 99%
“…QUE can attenuate liver injury [56] and renal impairment [57], [58], and provide neuroprotective protection against excitotoxic insults [59], [60]. KAE can also provide cardio- and neuro-protections [61].…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type zebrafish embryos (1 days post fertilization (dpf)) were treated with pure compounds or fractionsin zebrafish model for 2 days. After treatment, anti-tyrosine hydroxylase (TH) whole-mount immunostaining was performed using literature reported method5758. Zebrafish were fixed in 4% paraformaldehyde in PBS for 5 h, rinsed, and stored at −20 °C in 100% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies have shown that quercetin antagonizes cell toxicity induced by various oxidants and other neurotoxic molecules believed to act by inducing oxidative stress [1115]. In addition, several studies show that quercetin can exert neuroprotection and antagonize oxidative stress when administered in vivo .…”
Section: Introductionmentioning
confidence: 99%